THE IMPACT OF MOBILE APPLICATIONS ON HEALTHY LIFESTYLES AND CHRONIC DISEASE MANAGEMENT - Joanna Barwacz; Dagmara Gładysz; Magdalena Adamik; Layla Settaf-Cherif; Katarzyna Malinowska; Elhatra Settaf-Cherif (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Mobile applications (mHealth) are playing an increasingly important role in promoting healthy lifestyles and supporting patients with chronic diseases. Evidence from evidence-based medicine (EBM) studies indicates that they can support behavioral change, improve clinical parameter control and facilitate contact with the healthcare system.Objective: The aim of this study was to present current scientific evidence on the effectiveness of mobile applications in the field of health, with particular emphasis on behavioral and social effects.Methods: Systematic reviews, meta-analyses and randomized trials on the use of mobile applications for physical activity, weight loss, diabetes control, hypertension and other chronic diseases, as well as for improving adherence to pharmacotherapy recommendations, were included. Reports on data security, digital inequalities and WHO recommendations on mHealth were also analyzed.Results: According to meta-analyses, diabetes management apps lead to a significant reduction in HbA1c (by ~0.5% on average), especially when they are part of integrated clinical care. Apps that remind users to take their medication improve health behaviors related to pharmacotherapy, while those that promote physical activity and diet promote moderate, short-term weight loss and increased physical activity. Interventions using behavior change techniques such as self-monitoring, feedback and reminders are most effective. Positive social effects include increased motivation through support networks and facilitation of telemonitoring, but there are challenges related to data security, digital inequalities and lack of standardization in app quality.Conclusions: Mobile applications have potential as a tool to support the prevention and management of chronic diseases, but their effectiveness is moderate and variable. Further long-term randomized trials and the implementation of quality and safety standards are needed to fully exploit their clinical and social potential.